2016
DOI: 10.1021/acsami.6b01103
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Related Luminescent Hydroxyapatite-Enhanced Osteogenic Differentiation of Bone Mesenchymal Stem Cells Via an ATP-Induced cAMP/PKA Pathway

Abstract: Novel defect-related hydroxyapatite (DHAP), which combines the advantages of HAP and defect-related luminescence, has the potential application in tissue engineering and biomedical area, because of its excellent capability of monitoring the osteogenic differentiation and material biodegradation. Although the extracellular mechanism of DHAP minerals and PO4(3-) functioning in osteogenic differentiation has been widely studied, the intracellular molecular mechanism through which PO4(3-) mediates osteogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 46 publications
1
46
0
2
Order By: Relevance
“…BMSCs are capable of osteogenic differentiation, which indicates the prospect of the clinical application for biotherapy based on BMSCs (19). Osteogenic differentiation of BMSCs, in vitro and in vivo, has been extensively studied (20,21). The results of the present study demonstrated that glycitin promotes cell proliferation, osteoblast induction, and activates Col I mRNA expression and ALP activity of BMSCs.…”
Section: Discussionmentioning
confidence: 53%
“…BMSCs are capable of osteogenic differentiation, which indicates the prospect of the clinical application for biotherapy based on BMSCs (19). Osteogenic differentiation of BMSCs, in vitro and in vivo, has been extensively studied (20,21). The results of the present study demonstrated that glycitin promotes cell proliferation, osteoblast induction, and activates Col I mRNA expression and ALP activity of BMSCs.…”
Section: Discussionmentioning
confidence: 53%
“…activators, was detected before 50,51 and has a biomedical potential that extends beyond the scope of this study. 52,53 PL spectroscopy was used next to determine the type of defects present in ACP and HAp. The room temperature PL spectra are presented in Figs.…”
Section: F Structural Metastability and Surface Defectsmentioning
confidence: 99%
“…9 We previously reported that defect-related luminescent hydroxyapatite could enhance osteogenic differentiation of BMSCs via an ATP-induced cAMP/PKA pathway. 10 Doostmohammadi et al conrmed that bone-derived HA were compatible with BMSCs and HAPs could be used for bone tissue engineering. 11 Sun et al used primary osteoblastic cells as model to detect the biocompatibility of different-sized HAPs, and found that larger HAPs had a good biocompatibility with primary osteoblastic cells while smaller-sized HAPs can both promote osteoclast activity and restrain osteoblasts activity, implying that size-dependent cytotoxicity of HAPs.…”
Section: Introductionmentioning
confidence: 99%